Untapped Resources: Biotechnological Potential of Peptides and Secondary Metabolites in Archaea. (4th October 2015) - Charlesworth, James C.; Burns, Brendan P.
Abstract : Archaea are an understudied domain of life often found in "extreme" environments in terms of temperature, salinity, and a range of other factors. Archaeal proteins, such as a wide range of enzymes, have adapted to function under these extreme conditions, providing biotechnology with interesting activities to exploit. In addition to producing structural and enzymatic proteins, archaea also produce a range of small peptide molecules (such as archaeocins) and other novel secondary metabolites such as those putatively involved in cell communication (acyl homoserine lactones), which can be exploited for biotechnological purposes. Due to the wide array of metabolites produced there is a great deal of biotechnological potential from antimicrobials such as diketopiperazines and archaeocins, as well as roles in the cosmetics and food industry. In this review we will discuss the diversity of small molecules, both peptide and nonpeptide, produced by archaea and their potential biotechnological applications.